2017
DOI: 10.1080/14767058.2017.1325864
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome in pregnancy with polyhydramnios in comparison with normal pregnancy in department of obstetrics at Shiraz University of Medical Sciences

Abstract: Idiopathic polyhydramnios should be considered as a high-risk pregnancy that warrants close surveillance. More studies should be done to detect the best time and interval of fetal surveillance in these patients. Chromosomal and torch studies can determine the definite cause of polyhydramnios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Polyhydramnios risk factors include gestational diabetes mellitus, placental abnormalities, isoimmunization, multiple gestations, congenital anomalies, and chromosomal aberrations. If these risk factors are not present, then an "IP" diagnosis is made [4]. Approximately two-thirds of polyhydramnios cases are classified as IP [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyhydramnios risk factors include gestational diabetes mellitus, placental abnormalities, isoimmunization, multiple gestations, congenital anomalies, and chromosomal aberrations. If these risk factors are not present, then an "IP" diagnosis is made [4]. Approximately two-thirds of polyhydramnios cases are classified as IP [14].…”
Section: Discussionmentioning
confidence: 99%
“…Institutional guidelines do not include recommendations for the follow-up of IP patients. Because this population displays an increased risk for preterm labor [10,17], it is imperative to closely monitor IP high-risk pregnancies [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis of idiopathic hydramnios is not without implication for outcome. Even in the absence of a pathology explaining hydramnios, Asadi et al reported a higher risk of low birth weight (<2500 g), macrosomia (>4000 g), but also admission to intensive care, fetal distress at birth, fetal death, and poor adaptation to extra‐uterine life, premature birth and neonatal death in cases of idiopathic hydramnios compared to normal fluid pregnancies 44 . A 2020 French study also found 24.1% of unfavorable outcomes in cases of idiopathic hydramnios 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, Langer et al 14 Ainda em relação a marcadores ultrassonográficos de prognóstico fetal, descreve-se tendência a maior ocorrência de alterações de vitalidade fetal em casos de gastrosquise complicada por herniação de estômago e/ou bexiga urinária 19,20 . Paralelamente, o achado ultrassonográfico de polidrâmnio associa-se a maior risco de gastrosquise complexa 6,21 e, teoricamente, a maior risco de prematuridade secundária à sobredistensão uterina [22][23][24] .…”
Section: Objectivesunclassified